Loss of GET pathway orthologs in Arabidopsis thaliana causes root hair growth defects and affects SNARE abundance - Xing, Shuping; Denninger, Philipp; Schmidt, Vanessa Aphaia Fiona; Großmann, Guido (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Root hairs are unicellular extensions of the rhizodermis, providing anchorage and an increase in surface area for nutrient and water uptake. Their fast, tip-focused growth showcases root hairs as an excellent genetic model to study physiological and developmental processes on the cellular level. We uncovered a root hair phenotype that is dependent on putative Arabidopsis orthologs of the Guided Entry of Tail-anchored (TA) proteins (GET) pathway, which facilitates membrane insertion of TA proteins in yeast and mammals. We found that plants have evolved multiple paralogs of specific GET pathway components, albeit in a compartment-specific manner. In addition, we show that differential expression of pathway components causes pleiotropic growth defects, suggesting alternative pathways for TA insertion and additional functions of GET in plants., Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins are key players in cellular trafficking and coordinate vital cellular processes, such as cytokinesis, pathogen defense, and ion transport regulation. With few exceptions, SNAREs are tail-anchored (TA) proteins, bearing a C-terminal hydrophobic domain that is essential for their membrane integration. Recently, the Guided Entry of Tail-anchored proteins (GET) pathway was described in mammalian and yeast cells that serve as a blueprint of TA protein insertion [Schuldiner M, et al. (2008) Cell 134(4):634-645; Stefanovic S, Hegde RS (2007) Cell 128(6):1147-1159]. This pathway consists of six proteins, with the cytosolic ATPase GET3 chaperoning the newly synthesized TA protein posttranslationally from the ribosome to the endoplasmic reticulum (ER) membrane. Structural and biochemical insights confirmed the potential of pathway components to facilitate membrane insertion, but the physiological significance in multicellular organisms remains to be resolved. Our phylogenetic analysis of 37 GET3 orthologs from 18 different species revealed the presence of two different GET3 clades. We identified and analyzed GET pathway components in Arabidopsis thaliana and found reduced root hair elongation in Atget lines, possibly as a result of reduced SNARE biogenesis. Overexpression of AtGET3a in a receptor knockout (KO) results in severe growth defects, suggesting presence of alternative insertion pathways while highlighting an intricate involvement for the GET pathway in cellular homeostasis of plants.
Gesehen am 06.09.2018